The effects of different essential fruit juice and their combination on Saccharomyces cerevisiae cell growth - Aslan, Abdullah (Progress in Nutrition, 2014)
In this study, 15 groups were composed. i: Control group, ii: H2O2 group, iii: Strawberry + H2O2 juice group, iv: Banana juice + H2O2 group and v: Strawberry + Banana juice + H2O2 group. 1: Control group, 2: H2O2 group, 3: Apple + H2O2 juice group, 4: Watermelon juice + H2O2 groups and 5: Apple + Watermelon juice + H2O2 group. A: Control group, B: H2O2 group, C: Cherry + H2O2 juice group, D: Peach juice + H2O2 groups and E: Cherry + Peach juice + H2O2 group. After sterilization, fruit juice (20%) and H2O2 (6% v/v) were inserted to Saccharomyces cerevisiae (S. cerevisiae) cultures and the cultures were developed at 37°C for 1h, 3h, 5h and 72 hours (overnight). S. cerevisiae cell growth was determined by spectrophotometer. With respect to our studies results; cell growth rised in fruit juice groups to which Strawberry, banana, apple, watermelon, cherry, peach was taken in proportion to the positive control (H2O2) group at different growing times (1, 3, 5 and 72 hours) (p<0,05). As a result different fruit juices and their combination has a protective role for decrease the oxidative damage and increased cell growing in S. cerevisiae.